(untitled) (Vietnam Journal of Community Medicine, 2026)
Introduction: Ocular myasthenia gravis is an acquired autoimmune disorder, accounting for a small proportion of myasthenia gravis cases. It is considered a mild form that may precede progression to generalized myasthenia gravis. Current treatment strategies mainly focus on symptom control. Evidence supporting the use of traditional medicine approaches remains limited, and research in Vietnam is still scarce. This report presents a case in which the surrounding needling technique was applied in the treatment of ocular myasthenia gravis. Case description: We describe a 21-year-old male patient with recurrent, asymmetric ptosis diagnosed with ocular myasthenia gravis. The patient underwent surrounding needling acupuncture at ocular acupoints for 10 consecutive days. Clinical indicators, including the degree of ptosis, ocular motility, visual field, eye fatigue, and nocturnal dyspnea, were collected before treatment, were monitored throughout the acupuncture course, and were re-evaluated after completion to assess treatment efficacy. Discussion: Following treatment, the patient exhibited marked improvement in ptosis, visual field, and ocular motility. Conclusions: The surrounding needling technique, a traditional acupuncture method in Oriental medicine, demonstrated significant therapeutic benefits in the management of ocular myasthenia gravis and contributed to improved quality of life.